2016
DOI: 10.2967/jnumed.116.185975
|View full text |Cite
|
Sign up to set email alerts
|

Validation of MRI Determination of the Penumbra by PET Measurements in Ischemic Stroke

Abstract: The concept of the ischemic penumbra was formulated on the basis of animal experiments showing functional impairment and electrophysiologic disturbances with decreasing flow to the brain below defined values (the threshold for function) and irreversible tissue damage with blood supply further decreased (the threshold for infarction). The perfusion range between these thresholds was termed the "penumbra," and restitution of flow above the functional threshold was able to reverse the deficits without permanent d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
40
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 59 publications
(57 reference statements)
2
40
0
Order By: Relevance
“…We also examined effects of M2CAO and reperfusion on the absolute levels of OEF and CMRO 2 in severely ischemic but still viable tissue. These regions were outlined in CBF maps as tissue with normal perfusion but CBF levels of 12-22ml/100 g/min which is consistent with levels attributed to the penumbra (132). Healthy contralateral regions were used as controls.…”
Section: Discussionmentioning
confidence: 99%
“…We also examined effects of M2CAO and reperfusion on the absolute levels of OEF and CMRO 2 in severely ischemic but still viable tissue. These regions were outlined in CBF maps as tissue with normal perfusion but CBF levels of 12-22ml/100 g/min which is consistent with levels attributed to the penumbra (132). Healthy contralateral regions were used as controls.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of a biobridge is a novel mechanism which describes how cell grafts can engage in injury-specific migration between neurogenic and non-neurogenic sites whereby normal cellular motility is restricted. Both in vitro and in vivo results have shown that transplantation of SB623 cells can improve the histopathological and behavioral deficits associated not only with TBI, but also with stroke, spinal cord injury, and Parkinson's disease (Wang et al, 1996; Tang et al, 1998; Chiang et al, 2001; Failor et al, 2010; Rinholm et al, 2011; Xiong et al, 2011; Merson and Bourne, 2014; Buono et al, 2015; Ranasinghe et al, 2015; Heiss and Zaro-Weber, 2017). …”
Section: Injury-specific Stem Cells Migration Between the Neurogenic mentioning
confidence: 99%
“…Thus, a more in-depth understanding of the concept of the stem cell-paved biobridge in neurodegenerative diseases potentially amendable by this therapeutic action, including ischemic stroke, hypoxic-ischemic encephalopathy (HIE), and cerebral palsy (CP) among others, may yield important therapeutic benefits (Tajiri et al, 2014). These disorders are each characterized, in part, by sites of cellular degeneration, separated from neurogenic areas of the brain that could otherwise facilitate the recovery of severe damaged cells (Failor et al, 2010; Rinholm et al, 2011; Xiong et al, 2011; Tajiri et al, 2013; Merson and Bourne, 2014; Tajiri et al, 2014; Duncan et al, 2015; Ranasinghe et al, 2015; Heiss and Zaro-Weber, 2017). …”
Section: Potential Therapeutic Benefits Of Biobridge Formation In Strmentioning
confidence: 99%
See 1 more Smart Citation
“…PET imaging measures O 2 by detecting positron emitting radionuclides of a hypoxia biomarker, and has been used extensively and noninvasively in various in vivo brain and ischemic stroke studies 495051525354. Disadvantages to PET imaging is availability and the cost of cyclotrons needed to produce short-lived radionuclides, various interferences in the interpretation of PET imaging data, and PET measures O 2 consumption but not tissue pO 2 .…”
Section: Oximetry Methods For Cerebral Po2 Measurementsmentioning
confidence: 99%